The Morphosyntax of Middle Voice in Uab Meto - Naniana N. Benu; Risman Iye; Asriani Abbas (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2022)
This study focused on middle voice in Uab Meto. The point of this study is to describe the morphosyntactic element of the middle voice in Uab Meto. There are three forms of middle voice constructions in Uab Meto, namely reflexive, reciprocal, and lexical. A subject-reflective enclitic demonstrates the middle's reflexivity. Ma-, which is usually linked to the verb, signifies reciprocity. es nok es "each other" (lit. "one with one") is an additional signal that the construction is reciprocal, but its use is optional. There is a lexical middle verb type that is unmarked and syntactically intransitive. The argument's interpretation depends on the speaker's perceptions of the circumstances.